(untitled) (Asian Journal of Social Science Studies, 2022)
With the development of web2.0 era, the audience’s right to speak has played an increasingly important role in communication activities. Since the we-media emerged in endlessly, everyone can spread something. This has led to many media ethics problems, a large part of which is media trial. This article will be based on the “Cargo Lala Incident” and analyze the media trial.